Human cerebral cortex Cajal-Retzius neuron: development, structure and function. A Golgi study - Marín-Padilla, Miguel (Frontiers in Neuroanatomy, 2015)
The development, morphology and possible functional activity of the Cajal-Retzius cell of the developing human cerebral cortex have been explored herein. The C-RC, of extracortical origin, is the essential neuron of the neocortex first lamina. It receives inputs from subcortical afferent fibers that reach the first lamina early in development. Although the origin and function of these original afferent fibers remain unknown, they target the first lamina sole neuron: the C-RC. The neuron’ orchestrates the arrival, size and stratification of all pyramidal neurons (from ependymal origin) of the neocortex gray matter. Its axonic terminals spread radially and horizontally throughout the entire first lamina establishing contacts with the dendritic terminals of all gray matter pyramidal cells regardless of size, location and/or eventual functional roles. While the neuron axonic terminals spread radially and horizontally throughout the first lamina, the neuron’ bodies undergoes progressive developmental dilution and locating any of them in the adult brain become quite difficult. The neuron bodies are probably retained in the older regions of the developing neocortex while their axonic collaterals will spread throughout its more recent ones that, eventually, will represent the great majority of the brain surface. This will explain their bodies progressive dilution in the developing neocortex and, later, in the adult brain. Although quite difficult to locate the body of any of them, they have been described in the adult brain.